1994
DOI: 10.1073/pnas.91.16.7792
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hepatitis C virus infection in chimpanzees after antibody-mediated in vitro neutralization.

Abstract: Hepatitis C virus (HCV) is the most important etiologic agent of non-A, non-B hepatitis and is a major cause of chronic liver disease and hepatocellular carcinoma. Development ofan effective vaccine would be the most practical method for prevention of the infection, but whether infection with HCV elicits protective immunity in the host is unclear. Neutralization of HCV in vitro was attempted with plasma of a chronically infected patient, and the residual infectivity was evaluated by inoculation of eight serone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
320
1
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(330 citation statements)
references
References 37 publications
4
320
1
5
Order By: Relevance
“…Whether or not the typical antibodies measured in these studies conferred or was a marker of sterilizing immunity is controversial. In vivo studies in chimpanzees showed that the HCV-specific antibodies, specific for the HVR and with in vitro neutralizing ability, had protective effects against HCV infection [65]. On the other hand, other studies demonstrated that anti-HVR antibodies could not confer protective immunity against reinfection with homologous or heterologous strains [66; 67].…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%
“…Whether or not the typical antibodies measured in these studies conferred or was a marker of sterilizing immunity is controversial. In vivo studies in chimpanzees showed that the HCV-specific antibodies, specific for the HVR and with in vitro neutralizing ability, had protective effects against HCV infection [65]. On the other hand, other studies demonstrated that anti-HVR antibodies could not confer protective immunity against reinfection with homologous or heterologous strains [66; 67].…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%
“…Two HVRs (HVR1 and HVR2) in the E2 envelope glycoprotein have been identified. 52,53 At least 1 study has suggested that the early appearance of HVR1 antibodies is associated with an acute self-limiting HCV infection. 54 Additionally, mutations within certain regions, especially the E2 HVR, have been associated with the emergence of virus resistance to neutralization and the persistence of infection.…”
Section: Humoral Immune Responsesmentioning
confidence: 99%
“…In vitro preincubation of a standardized infectious HCV inoculum with the putative neutralizing serum or purified immunoglobulin G (IgG) showed that some challenged naïve chimpanzees were protected from HCV infection. 51,52 Although these results heralded enthusiasm on possible passive immunization strategies against HCV, the step toward clinical application proved to be more difficult. Postexposure prophylaxis of one chimpanzee with high amounts of anti-HCV IgG at 1 hour after its experimental inoculation did not prevent HCV infection.…”
Section: The Chimpanzee Model For Hcv Infectionmentioning
confidence: 99%